2017
DOI: 10.5152/tjar.2015.54872
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of the First Propofol Addiction in Turkey

Abstract: Propofol is a potent anaesthetic drug and also an effective sedative agent. Also, propofol may be used for non-anaesthetic purposes such as the treatment of seizures, migraine and tension headache in clinical practice. It has been abused, particularly among healthcare providers with high mortality rate. This report presents the case of a propofol-dependent patient who was an emergency medicine doctor with no difficulties in obtaining the drug. He himself visited our clinic for the treatment of propofol depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Short acting time, fast recovery, and few side effects are the advantages of propofol in clinical practice. Unconsciousness occurs 30 s after the 1.5-2.5 mg/kg propofol injection and lasts up to 10 min [4,5]. It is generally recognized to be safe for anesthesia and sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Short acting time, fast recovery, and few side effects are the advantages of propofol in clinical practice. Unconsciousness occurs 30 s after the 1.5-2.5 mg/kg propofol injection and lasts up to 10 min [4,5]. It is generally recognized to be safe for anesthesia and sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Its safety and possible side effects to patients are of great concern. Studies have revealed that propofol causes damage to neurons in the developing brain in rodents (Tagawa et al, 2014; Chen et al, 2016) and induces addictive behaviors in rodents and humans (Koopmann et al, 2011; Bonnet and Scherbaum, 2012; Lian et al, 2012; Earley and Finver, 2013; Koroglu and Tezcan, 2016; Wang et al, 2016; Wu et al, 2016). Propofol is often used as an analgesic or sedative in humans during in vitro fertilization procedures, and it accumulates in the follicular fluid of oocytes (Christiaens et al, 1999; Ben-Shlomo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%